How countries can reduce child stunting at scale: Lessons from exemplar countries - Bhutta, Zulfiqar A.; Akseer, Nadia; Keats, Emily C.; Vaivada, Tyler; Baker, Shawn; Horton, Susan E.; Katz, Joanne; Menon, Purnima; Piwoz, Ellen; Shekar, Meera; Victoria, Cesar; Black, Robert (American Society for Nutrition, 2020)
Child stunting and linear growth faltering have declined over the past few decades and several countries have made exemplary progress.